A Literary Study on the Applied Aspects of Udvartana on Medo Vikara - Pradhan, Subhrakanta; Sahoo, Manoj Kumar; Das, Arun Kumar; Dash, Biswajit (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda is the first medical science on earth. Ayurvedic medicine is an illustration of a traditional health-care system that is well-organized and widely used in several parts of Asia. It offers both preventive and therapeutic care. There are seven types of tissues in the human body known as Dhatus which holds our body structure. When all the Dhatus in the body are in their optimum levels, each of them contributes toward the health of the body. However, when there is vikriti in any of the Dhatus then it surely affects body nutrition, health, and mind. Medo vikaras are one of the best examples of the diseases caused due to vikriti in Medodhatu. Medodushti includes several types of Medo vikara, which are collectively known as Medoroga. Medoroga can be included in Santarpanjanya vyadhi. Medo Vikaras are mainly due to imbalance of energy of the body. It is a condition produced by derangement of Agni, which leads to Amarasa. There is Medo Dhatwagni Mandya, leading to improper formation of Medo dhatu. The concept of Udvartana is described as a daily regimen and also in Medavikara is widely found in different literatures in Ayurveda. It is one of the Panchakarma therapies which differ from Abhyanga in its direction of application and pressure during the procedure. It is a simple and affordable procedure with no harmful effects. In this review article, a detailed assessment of the Udvartana including its importance and benefits is explained.